A Study of Impact of CD4 and BMI on Effectiveness of DOTS in HIV-TB Cases Registered in Hamidia Hospital Bhopal - Priyesh Marskole; Sunil Nandeshwar; D K Pal; Himanshu Sharma (Medsci Publications, 2018)
Background: TB is the leading cause of morbidity and mortality among people living with HIV. The treatment for TB is same for HIV infected as for non-HIV infected TB patients. The same criteria determine the treatment category for TB patients irrespective of the HIV Status. Objectives: The objectives were to study outcome of DOTS in HIV-TB cases; to study the comparison of outcome of DOTS in HIV-TB and TB cases; and to study effects of different factors on outcome of DOTS in HIV-TB and TB cases. Material and method: Hospital based cross-sectional study was carried out in ART and DOTS center. 98 cases of HIV-TB co-infection and 150 cases of only TB infection were interviewed and BMI and CD4 of all cases of both the group were collected. All cases were observed to see the outcome and factors affecting outcome were studied separately. Result: cure rate in HIV-TB cases was 12.2% and in TB was 40%. Treatment completion rate was 51% in HIV-TB and 19.3% in TB cases. The study found that BMI was affecting outcome in both group while CD4 count affecting outcome in HIV-TB cases. Conclusion: The study indicated that cure rate improved as BMI and CD4 count increased.